A Fluorescent Guanosine Dinucleoside as a Selective Switch‐On Sensor for c‐myc G‐Quadruplex DNA with Potent Anticancer Activities. Issue 35 (29th July 2013) - Kumar, Y. Pavan; Bhowmik, Sudipta; Das, Rabindra Nath; Bessi, Irene; Paladhi, Sushovan; Ghosh, Rita; Schwalbe, Harald; Dash, Jyotirmayee
<x xml:space="preserve">Abstract</x> Like likes like! A novel fluorescent C2‐symmetric guanosine‐based dinucleoside has been engineered by chemical ligation of two guanosine units with a biocompatible dansyl tag. The nucleoside exhibits high selectivity for c‐myc G‐quadruplex DNA through fluorescence enhancement over duplex DNA and other promoter G‐quadruplexes (see scheme). It stains the nucleus preferentially, arrests the cell cycle at the G2/M phase, inhibits cell growth, and induces apoptosis in A375 cancer cells.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>